Legal Pluralism and Equity : Some Reflections on Land Reform in Cambodia - Adler, Daniel; Porter, Doug; Woolcock, Michael (World Bank, Washington, DC, 2018)
Institutional reforms in contemporary Cambodia are being undertaken in an environment characterized by pervasive legal pluralism the not uncommon situation in which numerous, contradictory and competing sets of rules and norms regulate social, economic and political relationships. The international development community has a long and unhappy history of engagement with such environments. This is not simply because the links between substantive policy and institutional arrangements in the 'transition to democracy' are many, uncertain and highly contingent. It is also the case because the formal precepts of liberal democracy as codified in new laws and regulations are often inconsistent with prevailing social norms and administrative practices. In fact, they may be fundamentally at odds with the interests of economic and political elites who have an interest in contesting, neutralizing or capturing institutions created under the new legal framework.